Rare myodocopid ostracods from Mesozoic sections of Hungary: summary, revision and description of new taxa - Tóth, Emőke; Cséfán, Tünde (Zootaxa, 2018)
With the exception of polycopids, Mesozoic myodocopid ostracods are regarded as uncommon in the fossil record. They are known from a few localities in the Tethys, and most of them are considered to be pelagic forms. However, a relatively rich and taxonomically diverse material is derived from Hungarian sections; these represent various formations deposited during the Triassic to Cretaceous. The aim of this study is to summarize the current knowledge of Mesozoic myodocopids and to provide new information concerning their classification and phylogenetic relations. This includes new occurrences of Triassic entomozoid Schallreuterizoe groosae Kozur, 2004, cylindroleberidid Triadocypris sp., cypridinid Palaeocypridina tulceaensis Sebe, 2013, Jurassic thaumatocyprid Pokornyopsis cf. bettenstaedti (Bartenstein, 1949) and P. feifeli (Triebel, 1941). The revision of the holotype of gigantic Triassic Triadogigantocypris balatonica Monostori, 1991 give new results concerning the valve structure and taxonomic position of the genus. Two new genera (Neorichterina n. gen. and Hungaroleberis n. gen.) and four new species (Neorichterina striata n. sp., Pokornyopsis csurgokutensis n. sp., Hungaroleberis retiferus n. sp. and Palaeocypridina goeroegae n. sp.) of the subclass Myodocopa are described. Moreover, most of the Albian to Cenomanian representatives of “Conchoecia” are newly classified as Entomozoidae (Neorichterina n. gen.), which allows to extend the range of the family up to the Cretaceous. A summary of the relevant assemblages present in Hungary will help to complement the existing, previously published literature on myodocopids, and also clarify details about the phylogenetic model of the group.